2005
DOI: 10.1021/ol047353d
|View full text |Cite
|
Sign up to set email alerts
|

Cycloruthenated Primary and Secondary Amines as Efficient Catalyst Precursors for Asymmetric Transfer Hydrogenation

Abstract: [reaction: see text] Ruthenacycles obtained by cyclometalation of enantiopure aromatic primary or secondary amines with [(eta6-benzene)RuCl2]2 or with [(eta6-p-cymene)RuCl2]2 are efficient catalysts for asymmetric transfer hydrogenation (TOF up to 190 h(-1) at room temperature). Enantioselectivities in the transfer hydrogenation of acetophenone ranged from 38% to 89%. It is possible to prepare the catalysts in situ, which allows the use of high throughput experimentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
67
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 115 publications
(71 citation statements)
references
References 38 publications
1
67
0
2
Order By: Relevance
“…Use of ruthenacycle 1a as catalyst (S:C = 100) in the asymmetric transfer hydrogenation of acetophenone, using iso-propanol as reductant and solvent and KOtBu as activator led to a 48% yield of 1-phenylethanol after 2 h with a product ee of 10% (Table 1, entry 1) [25].…”
Section: Ruthenacycles As Transfer Hydrogenation Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…Use of ruthenacycle 1a as catalyst (S:C = 100) in the asymmetric transfer hydrogenation of acetophenone, using iso-propanol as reductant and solvent and KOtBu as activator led to a 48% yield of 1-phenylethanol after 2 h with a product ee of 10% (Table 1, entry 1) [25].…”
Section: Ruthenacycles As Transfer Hydrogenation Catalystsmentioning
confidence: 99%
“…As we wanted to screen a broad range of chiral aromatic primary and secondary amines we decided to use a High Throughput Experimentation (HTE) approach. Indeed, we were able to automate both the synthesis of the ruthenacycles as well as their screening in the transfer hydrogenation using a Lizzy liquid dispensing robot that is positioned in a glovebox [25]. After completion of the ruthenacycle synthesis the solvent acetonitrile, which is an inhibitor for the transfer hydrogenation was removed by blowing nitrogen through the vials; iso-propanol was added, followed by the substrate acetophenone and finally a solution of KOtBu (1.5 equiv to Ru) to activate the catalyst.…”
Section: Ruthenacycles As Transfer Hydrogenation Catalystsmentioning
confidence: 99%
“…[38] It turns out these compounds are remarkably good catalysts for the asymmetric transfer hydrogenation of ketones. [39] Better still, it is possible to perform the catalyst synthesis in the robot, immediately followed by screening of its catalytic activity for the substrate of interest. It is necessary to remove the acetonitrile that was used as a solvent for the ruthenacycle synthesis, as it disturbs the catalytic activity in the transfer hydrogenation.…”
Section: Ruthenacycles For Asymmetric Transfer Hydrogenationmentioning
confidence: 99%
“…We therefore embarked on a study to evaluate a series of (RNH 2 )RuA C H T U N G T R E N N U N G (h 6 -arene) complexes with higher stabilities for their potential in alcohol racemization under DKR conditions. We were thereby inspired by recent publications of the groups of Pfeffer and Baratta, [16,17] who reported stable and synthetically readily accessible transfer hydrogenation Ru catalysts. Pfeffer and co-workers showed that chiral cycloruthenated primary and secondary amines can be synthesized cleanly in situ in a single step.…”
mentioning
confidence: 99%
“…Pfeffer and co-workers showed that chiral cycloruthenated primary and secondary amines can be synthesized cleanly in situ in a single step. [16] From this class of compounds complex 5 ( Figure 2) was included in this study. Another category of amine-containing ligands, are the 2-aminomethylpyridine (ampy) derivatives.…”
mentioning
confidence: 99%